Fear of falling and physical function in older adults with cataract: Exploring the role of vision as a moderator - Palagyi, A.; Ng, J.; Rogers, K.; Meuleners, Lynn; McCluskey, P.; White, A.; Morlet, N.; Keay, L. (Wiley Online Library, 2016)
Aim: To examine fear of falling and associated factors in a cohort of older adults with cataract, and investigate the interplay of vision and physical function with respect to fear of falling. Methods: We analyzed baseline data from a longitudinal study of adults aged ≥65 years referred for cataract surgery. Fear of falling was assessed by the Short Falls Efficacy Scale-International. Physical function was determined by the Short Physical Performance Battery. Participants underwent assessment of visual acuity, contrast sensitivity, visual disability, quality of life, depressive symptoms, exercise frequency, comorbidity and falls history. Factors associated with fear of falling were assessed using linear regression. Planned stepwise regression investigated vision as a potential moderator of the relationship between physical function and fear of falling. Results: Among 322 participants, 32.9 % (n = 106) showed high fear of falling. Poorer physical function, more comorbidities and greater visual disability were independently associated with a higher fear of falling (all P < 0.001). Visual disability moderated the relationship between physical function and fear of falling (β = −0.10, P = 0.04). The impact of physical function on fear of falling was strongest in participants with higher (+1 standard deviation above the mean) visual disability (b = −0.21, P < 0.001). Conclusions: Fear of falling in older adults with cataract is greatest in those with poorer physical function and higher levels of visual disability. Perceived visual ability has a moderating role in the relationship between physical function and fear of falling; physical function alone might not adequately predict falls concern.